Subthreshold multisensory processing in cat auditory cortex - Meredith, M. Alex (2009)
For multisensory processing to occur, inputs from different sensory modalities must converge onto individual neurons. Traditionally, multisensory neurons have been identified as those, which were independently activated by more than one sensory modality. Recently, a different multisensory search paradigm has revealed neurons in somatosensory and visual cortex that were activated by only a single modality, whose responses were significantly affected by the presence of a second modality cue. These experiments recorded neurons in the cat auditory field of the anterior ectosylvian sulcus that also met this criterion, suggesting that subthreshold forms of multisensory processing may represent a general feature of multisensory systems.